Karakterisasi katalis dari Zeolit Alam/KF menggunakan metode X-Ray Diffraction - Nurrizka, Zahra; Zamhari, Mustain; Yerizam, Muhammad (Jurnal Serambi Engineering, 2026)
Natural zeolite is a porous material with great potential as a heterogeneous catalyst, but its catalytic activity still needs to be improved. One way to improve the basic properties of zeolite is by modifying it using potassium fluoride (KF). This study aims to produce a strong base catalyst based on natural zeolite/KF and characterize its crystal structure using the X-Ray Diffraction (XRD) method. The catalyst synthesis process includes initial zeolite activation, impregnation with varying KF concentrations (1.5%–3.5%), and calcination at 500–700°C. The XRD characterization results show that the sample with a KF concentration of 2.5% and a calcination temperature of 600°C (code T248) produced the best catalyst, with a crystallite size of 176 Å and the lowest microstrain of 0.25%, as well as a very high degree of crystallinity. This indicates that these conditions are optimal for producing a stable and regular crystal structure. The catalyst produced in this study has the potential to be used in various chemical reaction applications, such as transesterification for biodiesel production.